2020
DOI: 10.31729/jnma.5314
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Position of Lower Third Molar in Relation to Mandibular Canal on Cone-Beam Computed Tomography Images in A Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: The positional relationship between the mandibularcanal with impacted mandibular third molar is the main factor of inferior alveolar nerve injury. The purpose of this study wasto classify the anatomical three dimensional relationship between the proximity of impacted mandibular third molars to the inferior alveolar canal. Methods: The descriptive cross-sectional study was conducted inthe Department of Oral and Maxillofacial Surgery of a tertiary care hospital from July 2020 to August 2020 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 2 publications
1
2
1
10
Order By: Relevance
“…This study included almost equal number of right and left MM3s which was consistent with result of previous study of Jadu, et al 7 On evaluating the position of the inferior alveolar canal with respect to the roots of MM3, our study showed that most canals were located inferior to the inferior alveolar canal which in similar to the studies by Gu, et al 22 and Chaudhary, et al 23 but in contrast to study by Ghaeminia, et al 11 and Karnasuta, et al 6 where in most cases, the inferior alveolar canals had lingual position. Less number of cases with lingual position of canals were seen in studies by Jadu, et al 7 , Gu, et al 22 , Chaudhary, et al 23 and Maglione, et al 24 Compression of inferior alveolar canal by the roots of MM3 was maximum 64.1% when the inferior alveolar canal was in lingual position in our study. Chaudhary, et al 23 reported the maximum number compression when inferior alveolar canal was placed lingually and Jadu, et al 7 reported the maximum compression when the canal was inferior to the MM3.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study included almost equal number of right and left MM3s which was consistent with result of previous study of Jadu, et al 7 On evaluating the position of the inferior alveolar canal with respect to the roots of MM3, our study showed that most canals were located inferior to the inferior alveolar canal which in similar to the studies by Gu, et al 22 and Chaudhary, et al 23 but in contrast to study by Ghaeminia, et al 11 and Karnasuta, et al 6 where in most cases, the inferior alveolar canals had lingual position. Less number of cases with lingual position of canals were seen in studies by Jadu, et al 7 , Gu, et al 22 , Chaudhary, et al 23 and Maglione, et al 24 Compression of inferior alveolar canal by the roots of MM3 was maximum 64.1% when the inferior alveolar canal was in lingual position in our study. Chaudhary, et al 23 reported the maximum number compression when inferior alveolar canal was placed lingually and Jadu, et al 7 reported the maximum compression when the canal was inferior to the MM3.…”
Section: Discussionsupporting
confidence: 91%
“…Less number of cases with lingual position of canals were seen in studies by Jadu, et al 7 , Gu, et al 22 , Chaudhary, et al 23 and Maglione, et al 24 Compression of inferior alveolar canal by the roots of MM3 was maximum 64.1% when the inferior alveolar canal was in lingual position in our study. Chaudhary, et al 23 reported the maximum number compression when inferior alveolar canal was placed lingually and Jadu, et al 7 reported the maximum compression when the canal was inferior to the MM3.…”
Section: Discussioncontrasting
confidence: 52%
“…Para minimizar estas complicaciones, es importante evaluar la posición de los terceros molares inferiores impactados y su contigüidad con el CAI apoyada de un examen radiográfico, la misma que es esencial para diagnosticar el grosor de las placas corticales, la ubicación del conducto y su relación con las raíces, además el grado de inclinación de los molares antes de realizar cualquier proceso quirúrgico, para prevenir algún trastorno neurosensorial del NAI (Badawy, 2016). Anteriormente, las radiografías panorámicas se recomendaban como método radiográfico primario, sin embargo, por la superposición de imágenes en estas radiografías, es difícil conocer la relación posicional del canal mandibular (CM) con precisión, especialmente en la dirección vestibulolingual (Chaudhary, 2020).…”
Section: Introductionunclassified
“…Algunos autores al observar las imágenes CBCT en condiciones de visualización ideales interpretaron y calificaron el recorrido del CAI en base a la relación horizontal entre el tercer molar mandibular y el CM, la relación vertical entre el tercer molar mandibular, el CM y la integridad de la pared del CM, de la siguiente manera: (Figura 1) a) Proyección recta: La última parte del canal mandibular estaba casi al mismo nivel que un agujero mentoniano; b) Configuración en catenaria: Canal mandibular curvado como colgando entre dos puntos; c) Descenso progresivo: Descenso del canal mandibular de posterior a anterior (Chaudhary, 2020;Ozturk,2012).…”
Section: Introductionunclassified
See 1 more Smart Citation